The Daptone super soul revue [compact disc] : live! at the Apollo. - Shelton, Naomi; Bradley, Charles, 1948-2017; Jones, Sharon, 1956-2016 (Daptone Records, 2021)
Daptone celebrates twenty years of soulful music with this release. Performed and recorded over three nights in front of a sold out crowd at The World Famous Theater in Harlem, NY (December 4th - 6th, 2014), this album brings the electrifying performances that helped put Daptone on the map. Featuring live sets from: Sharon Jones and the Dap-Kings, Charles Bradley and his Extraordinaires, Naomi Shelton and the Gospel Queens, Menahan Street Band, Saun & Starr, The Sugarman 3.